2021
DOI: 10.3389/fcimb.2021.613304
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Transcription Recombinase-Aided Amplification Assay With Lateral Flow Dipstick Assay for Rapid Detection of 2019 Novel Coronavirus

Abstract: BackgroundThe emerging Coronavirus Disease-2019 (COVID-19) has challenged the public health globally. With the increasing requirement of detection for SARS-CoV-2 outside of the laboratory setting, a rapid and precise Point of Care Test (POCT) is urgently needed.MethodsTargeting the nucleocapsid (N) gene of SARS-CoV-2, specific primers, and probes for reverse transcription recombinase-aided amplification coupled with lateral flow dipstick (RT-RAA/LFD) platform were designed. For specificity evaluation, it was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
(35 reference statements)
2
33
0
Order By: Relevance
“…Nowadays, the applications of RAA in the detection of viruses, bacteria, and parasites are being widely explored. For example, Zheng et al [ 24 ] established an RT-RAA-LFD assay for the rapid diagnosis and endemic monitoring of Coronavirus Disease-2019. Zhang et al [ 25 ] developed a real-time fluorescence RAA detection to monitor foodborne salmonella contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the applications of RAA in the detection of viruses, bacteria, and parasites are being widely explored. For example, Zheng et al [ 24 ] established an RT-RAA-LFD assay for the rapid diagnosis and endemic monitoring of Coronavirus Disease-2019. Zhang et al [ 25 ] developed a real-time fluorescence RAA detection to monitor foodborne salmonella contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, minimal requirements for equipment and resources make it especially suitable for on-site inspection in the underdeveloped areas, which has broad application prospects ( Li et al., 2020 ). It was reported that the established POCT assay-based RAA offered 100% specificity and 100% sensitivity in the detection of clinical respiratory tract samples from COVID-19 patients when compared with RT-PCR ( Xue et al., 2020 ; Zheng et al., 2021 ). Additionally, a multiple-center clinical evaluation of RT-RAA kit using respiratory tract samples (throat swabs, sputum, nasopharyngeal swabs, nasal swabs and bronchoalveolar lavage fluid) and non-respiratory samples (stool and whole blood) show that the total coincidence rate was 97.78% and the kappa value 0.952 (p < 0.05) compared to the commercial RT-PCR kits ( Wang J. et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These formats include exo probe, nfo probe, fpg probe, digital ( Shen et al, 2011 ), nesting, microfluidics ( Lutz et al, 2010 ), solid phase, template generation, electrochemistry, colorimetric or SNP detection, and so on ( Daher, Stewart, Boissinot, & Bergeron, 2016 ; Li et al, 2020 ). Among all these, it seems that using exo probe for fluorescence detection ( Behrmann et al, 2020 ; Tu et al, 2020 ) and using nfo probe coupled with lateral flow strip detection ( Zheng et al, 2021 ) are the most popular and hence we will mainly focus on these two formats for the detection of SARS-CoV-2 viral RNA by RT-RPA. Herein, either approach has its own advantages.…”
Section: Sensitive Detection Of Sars-cov-2 Via Rt-rpamentioning
confidence: 99%
“…Until now, there have been multiple reports about the detection of SARS-CoV-2 viral RNA using RT-RPA approach following our initial report in March 2020 and May 2020 ( Abd El Wahed et al, 2021 ; Arizti-Sanz et al, 2020 ; Behrmann et al, 2020 ; Qian et al, 2020 ; Tu et al, 2020 ; Wang, Cai, et al, 2020 ; Xia and Chen, 2020a , Xia and Chen, 2020b ; Xiong et al, 2020 ; Xue et al, 2020 ; Zheng et al, 2021 ). We introduced an WEPEAR ( w hole-course e ncapsulated p rocedure for e xponential a mplification from R NA) that seamlessly combines the reverse transcription (optimally at 37 °C, in the absence of Mg(OAc) 2 catalyst) and the RPA reaction (optimally at 40 °C, in the presence of Mg(OAc) 2 catalyst) at their own optimal conditions ( Fig.…”
Section: Comparative Reviews Of Recently Published Rt-rpa Assays For Sars-cov-2 Detectionmentioning
confidence: 99%